Factors Influencing Indonesian Dairy Farmers in Making Business Decisions - Putro, Utomo Sarjono; Alamanda, Dini Turipanam; Utami, Hesty Nurul; Siallagan, Manahan; Nirmala, Shena Nadya (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. The development of the dairy industry in Indonesia is concentrated in Java and is dominated by the traditional farm with small-scale ownership, which is farmers do not get a big profit, farm management is very simple, farmers low level of education, and most farmers have dairy cattle that functioned as savings. This research was conducted to answer questions about how the behavior and decisions of farmers are influenced by interactions with other agents or factors; and how to encourage farmers to increase the cattle population and milk production so that farmers' income increases and have a sustainable business farm to develop the dairy industry in Bandung Regency. Agent-based modeling was conduction with the help of the SOARS program.  In this research, dairy farmers are categorized into three clusters using cluster analysis, which is, the motivated, the survived, and the unsatisfied. Agent-based modeling is suitable for the complexities of this research which are the motivation, behavior, decision, and interactions of dairy farmers will be affecting the output of the dairy industry system as a whole; and to implement some policy scenarios. Keywords:  Agent-based, dairy farmer, milk production, business decisions, behaviour